Kajian Atas Naskah Kitab Al-Nikah - Ahmad Rofii (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2012)
The article examines a manuscript entitled Kitab al-Nikah (KN) written by Abu 'Abd Allah al-Husayn ibn Ahmad al-Mahfani, a writer who is assumed to be from Jawi land (Nusantara). KN is a digest book of marriage law according to the Syafi’i school. The explanation and sentences used in this manuscript refer to the major sources of the Syafi’i school literature. What is quite uniqe of are as follow: first, unlike the majority of the digest literature of law, KN provides legal basis that come from al-Qur’an and hadis upon certain rules of marriage law. Second, KN employs an approach of comparative law, particularly with Abu Hanifah and Malik schools. This is certaintly uncommon for a digest book. Third, KN provides important additional information on Islamic basis of morality such as its reference to the principle of prudence and wara’, and its emphasis on the principle of no-harm and good relationship between husband and wife, something rarely found in the classical fiqh literature.